Produção de gesso reciclado a partir de resíduos oriundos da construção civil. - Ribeiro, Abrahão Severo (2006)
Comparing to others binders, as Portland cement and lime, plaster is much more energetic efficient because it can be obtained at relatively low temperatures (less than 160oC). During its making process, it emits water vapor to atmosphere, instead CO2 produced by the others binders named above. Although, being a calcium sulfate that has some water solubility, irregular deposition of its residues can contaminate ground and natural source of water The resolution 307/02 of Brazilian National Environmental Council considers plaster as class C material, so, a material that generates residues for those technologies or feasible applications were not still developed to permit a recycling. Then, it is necessary to change this reality and to find a way to minimize plasters residues to environment. In this work, a possibility to obtain plaster from residues of four of its applications in civil construction (coating, sealing plates, decoration pieces, ceramic moulds) was investigated. Initially, the plaster residues volume generated at Recife Metropolitan Area was researched. After, physical, chemical and mechanical properties were obtained. X ray difractometry showed much alike between the recycled plasters and natural plaster. The same occurred with mechanical strength. Despite some small differences on others properties (as lower initial and final set time) results indicate that it is possible to recycle plaster residues. For this it is necessary to separate it of others construction materials residues in the construction site